Current problems of professional training of service specialists - Ihor Vasilievich Hevko (Kazimierz Wielki University, 2020)
The article is devoted to the current problem of professional training of future specialists in the field of services. The article describes the main features of the organization of professional training of specialists in the service sector, which form a complex of professionally important skills. The possibility of theoretical and pedagogical training of future specialists in the field of services is described. The article emphasizes that professional skills of service professionals have a complex structure and are formed in the process of learning and further professional activity. The high level of professional skills of service professionals will contribute to the development of a highly qualified specialist in the labor market, while respecting all the pedagogical conditions of professional skills formation.